Clinicopathologic features of single bone metastasis in breast cancer. Issue 1 (8th January 2021) - Karatas, Murat; Zengel, Baha; Durusoy, Raika; Tasli, Funda; Adibelli, Zehra; Simsek, Cenk; Uslu, Adam
Abstract : Abstract: The most common site for metastasis in patients with breast cancer is the bone. In this case series, we investigated patients whose surgical and medical treatment for primary breast cancer was conducted at our center and first disease recurrence was limited to only 1 bone. We analyzed 910 breast cancer patients, 863 had no metastasis and 47 cases had a single bone metastasis ≥ 6 months after their first diagnosis. Demographic, epidemiological, histopathological and intrinsic tumor subtype differences between the non-metastatic group and the group with solitary bone metastases and their statistical significance were examined. Among established breast cancer risk factors, we studied twenty-nine variables. Three variables (Type of tumor surgery, TNM Stage III tumors and mixed type (invasive ductalcarsinoma + invasive lobular carcinoma) histology) were significant in multivariate logistic regression analysis. Accordingly, the risk of developing single bone metastasis was approximately 15 times higher in patients who underwent mastectomy and 4.8 and 2.8 times higher in those with TNM Stage III tumors and with mixed type (invasive ductal carcinoma + invasive lobular carcinoma) histology, respectively. In conclusion, the risk of developing single bone metastasis is likely in non-metastatic patients with Stage III tumors and possibly in mixed type tumors. Knowing this risk, especially in patients with mixed type tumors, may be instrumental in taking measures with different adjuvant therapies in future studies. Among these, treatment modalities such as prolonged hormone therapy and addition of bisphosphonates to the adjuvant treatments of stage III and mixed breast cancer patients may be considered.